Diseño e implementación del control interno del inventario de la empresa Quindiana de Negocios S.A.S (2013)
The Quindiana company BUSINESS SAS was established from January 1, 2013 , by a group of pawnshop that worked independently of each other , because each pawnshop had a different owner , all these pawnshop at the head of their owners joined to form this company and to be more competitive in a difficult market , in each of these commercial establishments there were controls, which helped in its operation thereby minimizing the risks, but when joined , these controls were dispersed presenting failure this new company because even though there were controls in each these were not documented , so it was little clarity about what he had to do was for each person , often presenting these cases in people new within the company since in these cases the oldest were very sporadic, but evidencing the lack of an internal control system . The design and implement the system of internal control of inventory in the company will allow the staff responsible for its management to be clear on their roles and responsibilities , also contribute to other people who are related to this asset leave stipulated what their responsibilities and functions.